Bariery integracji Mołdawii z Unią Europejską – wymiar energetyczny - Rutkowski, Wojciech (Polityka i Społeczeństwo, 2020)
The article presents an analysis of energy barriers to integration between the Republic of Moldova and the European Union. Moldova is one of the most important objectives of external activity of the European Union in Eastern Europe. Nowadays, the energy market problems have a strong influence on the process of political and economic integration between Moldova and the EU. The biggest challenge for Moldova in the energy sector is to break the reliance on the supply of Russian fossil fuels, and to implement EU energy legislation, especially the rules of the third energy package. The article also emphasizes the impact of the conflict in Transnistria on EU-Moldova energy relations.